The Significance of Teacher-Students Relationship and Students’ Academic Achievement - Asrun Laksana; Amri Tanduklangi; Sartiah DP (Halu Oleo University, 2019)
Students at risk for school failure often experience a sense of alienation from school in addition to the more task-related problem of poor academic achievement. The hypothesis of this study is that the results will suggest that the social context of the classroom influences students' appraisals of school as a likeable and satisfying environment. The purpose of this study was to determine if the student-teacher relationship impacts students’ academic achievement. This research includes a quantitative methodology with respect to the perceptions of students/alumni of English Education Study Program regarding teacher- student relationship factors that impact academic achievement. Data gathered through a questionnaire, interview and relevant documents. Twenty-nine respondents participated in this study by filling out a questionnaire, and five students were interviewed to obtain more information related to their response to the questionnaire. This study resulted in three major conclusions: Teachers’ attitudes about students must be designed based on the needs of all students; the current structure of public education and professional learning communities must continue to increase student engagement in learning; and teacher education programs must incorporate the development of interpersonal skills and build meaningful student relationships within the classroom.Keywords:Teacher Students’ Relationship; Teacher Expectancy; Students Academic Achievement